2002
DOI: 10.1002/j.1556-6678.2002.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

White Racial Identity Attitudes and the Ego Defense Mechanisms Used by White Counselor Trainees in Racially Provocative Counseling Situations

Abstract: This exploratory study examined the relationship between racial identity attitudes and the use of ego defense mechanisms by White counselor trainees during cross-racial counseling and supervision dyads. The sample consisted of 145 White counselor trainees enrolled in both master's and doctoral programs at 2 small private universities located in the northeastern United States. Results indicated that White counselor trainees at less mature statuses of racial identity attitudes relied on more primitive ego defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Freud identified the defense of denial, displacement, intellectualization, and rationalization, each of which is similar to the domains and category descriptions of Denial, Deflection, Intellectualization, and Rationalization that emerged from this data analysis. Descriptions of Denial, Deflection, Intellectualization, Rationalization, and Minimization have been previously discussed by researchers as conceptual ideas in literature exploring the cognitive behavior aspects of resistance in multicultural classrooms (e.g., King, 2004;Mio & Awakuni, 2000;Thompson & Neville, 1999) and in an empirical investigation of the use of defense mechanisms in multicultural counseling (Utsey & Gernat, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Freud identified the defense of denial, displacement, intellectualization, and rationalization, each of which is similar to the domains and category descriptions of Denial, Deflection, Intellectualization, and Rationalization that emerged from this data analysis. Descriptions of Denial, Deflection, Intellectualization, Rationalization, and Minimization have been previously discussed by researchers as conceptual ideas in literature exploring the cognitive behavior aspects of resistance in multicultural classrooms (e.g., King, 2004;Mio & Awakuni, 2000;Thompson & Neville, 1999) and in an empirical investigation of the use of defense mechanisms in multicultural counseling (Utsey & Gernat, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also noted that given the power differential in favor of supervisors in the supervisory relationship, it is the supervisor's racial identity status that has a more powerful role in shaping interactions between supervisor and supervisee and between supervisee and client. Empirical studies have focused more on multicultural counseling competence and supervision experiences of supervisees (Burkard, Ponterotto, Reynolds, & Alfonso, 1999;Constantine, 2002;Gatmon et al, 2001;Utsey & Gernat, 2002) than on supervisors. Some researchers have focused on both supervisors and supervisees.…”
mentioning
confidence: 99%
“…The findings of this study provide some unique distinctions and commonalities with the existing literature on training White counselors for empathy, advocacy, and multicultural counseling competence. In terms of distinctions, Utsey and colleagues (Utsey & Gernat, ; Utsey, Hammar, & Gernat, ) found that White counselor trainees experience anxiety surrounding multicultural counseling. This theme was not present for participants in our study; instead, the counselors in our study discussed positive experiences with communities of color, learning from communities of color, and the common values and life experiences.…”
Section: Discussionmentioning
confidence: 99%